1999
DOI: 10.1021/la981046x
|View full text |Cite
|
Sign up to set email alerts
|

Particle Sizing in Colloidal Dispersions by Ultrasound. Model Calibration and Sensitivity Analysis

Abstract: In this paper, the use of ultrasonics for the determination of particle size distributions (PSDs) in suspensions and emulsions is discussed. Focusing on systems with a large density difference between the dispersed and continuous phases, a mathematical model is used to correlate the primary measurementthe attenuation of acoustic waves as a function of frequencyto the PSD, and it becomes clear that the quality of the PSD thus obtained is directly related to the accuracy of the model parameters. To overcome po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…According to a number of experimental data, the presence of particles in the suspension causes an increase in the absorption coefficient of the ultrasound wave, which is the greater the higher the concentration of the particles [27,35,36]. At a constant volume concentration this increase depends on the size of the magnetic particles, and the larger the particles the greater the absorption [36].…”
Section: Resultsmentioning
confidence: 99%
“…According to a number of experimental data, the presence of particles in the suspension causes an increase in the absorption coefficient of the ultrasound wave, which is the greater the higher the concentration of the particles [27,35,36]. At a constant volume concentration this increase depends on the size of the magnetic particles, and the larger the particles the greater the absorption [36].…”
Section: Resultsmentioning
confidence: 99%
“…In solid-in-liquid suspensions, the dominant phenomena are visco-inertial, through the coefficient A 1 , and it would seem reasonable to assume that an accurate knowledge of the density of the particles and the viscosity of the continuous phase would be required and that the thermal properties would be less important. Hipp et al have developed these ideas and have used a perturbation technique to fit a group of unknown physical properties when the sizes of the suspended particles were known accurately [6]. Babick et al showed the degree of dependency of Psd on the material properties when attenuation is assumed to be caused by either thermal or viscoinertial losses [36].…”
Section: Uncertainties In Physical Propertiesmentioning
confidence: 99%
“…The technique has been used by, for example, davis [3] to measure mass flow and particle size in coal slurries, Mcclements and Povey [4] to examine aqueous sunflower oil emulsions in the context of the food industry, and Holmes et al [5] to study aqueous suspensions of polystyrene and silica. It is generally recognized that ultrasonic wave attenuation is more sensitive than phase velocity to dispersed particle size [4], and so attenuation is the preferred variable for particle sizing [6]. There exists an international standard which applies to particle characterization by means of ultrasound attenuation spectroscopy [7].…”
mentioning
confidence: 99%
“…Ultrasonic attenuation and velocity measurements can be used for particle size monitoring in dispersed systems ( [71], see Section 3.3).…”
Section: Ultrasoundmentioning
confidence: 99%